2015
DOI: 10.1007/s12540-015-5164-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sn and Sb on the corrosion resistance of AH 32 steel in a cargo oil tank environment

Abstract: Effects of the alloying elements, Sn and Sb, on the corrosion resistance of modified AH 32 steel for the cargo oil tanks (COT) were examined using an electrochemical test and weight loss measurement. All experiments were carried out in acidic chloride solution (0.14 M HCl and 10 wt% NaCl, pH 0.85) at 30°C, simulating the inner bottom plate of COT. It was clearly found that the small amount addition of Sn and Sb improved the corrosion resistance of modified AH 32 steel, which is confirmed by the higher polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This then reacts with O 2 to generate a stable Sb 2 O 3 , which is deposited in the micropores and microcracks of the rust layer to increase the pH of the steel surface in the corrosive environment. This is conducive to the transformation of γ-FeOOH [28]. Therefore, the rust layer of Sb-containing steel is more stable than the remaining two steels, and the formation process of Sb 2 O 3 is as follows: Sb + 3H + + 3e − → SbH 3 ;…”
Section: Discussionmentioning
confidence: 99%
“…This then reacts with O 2 to generate a stable Sb 2 O 3 , which is deposited in the micropores and microcracks of the rust layer to increase the pH of the steel surface in the corrosive environment. This is conducive to the transformation of γ-FeOOH [28]. Therefore, the rust layer of Sb-containing steel is more stable than the remaining two steels, and the formation process of Sb 2 O 3 is as follows: Sb + 3H + + 3e − → SbH 3 ;…”
Section: Discussionmentioning
confidence: 99%
“…XPS spectra are shown in Figure 7 in the form of the Sb peaks and O peaks from the 0.10Sb steel after immersed 30 d. As for the Sb peak was not obviously, and always confused with the O peak, other peaks were separated from the XPS spectra, and the O peaks were separated for reference. And all these peaks are related to the binding energy of FeOOH, Fe 3 O 4 and Sb 2 O 3 (529.9 eV) (Ahn, 2015;Kamimura et al, 2012).…”
Section: Corrosion Product Film Analysismentioning
confidence: 99%
“…In the past few years, a Brazilian steel company started the development of antimony-based carbon steels for applications subject to the condensation of sulphuric acid and proved that Sb improved the corrosion resistance (Wu et al, 2020b;Lins et al, 2017;Zhang et al, 2013). Recently, it was found out that Sb addition improved the corrosion resistance of low-alloy steel in acid dew corrosion environment by Nippon Steel (Ahn, 2015;KOJIMA, 2004). However, the corrosion mechanism of Sbcontaining low-alloy steel in acid environment was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the addition of Sn and Sb can significantly improve the corrosion resistance of microalloyed steels [16][17][18]. Ahn, SooHoon, et al [19] found that SnO 2 and Sb 2 O 5 , the protective corrosion products produced by microalloyed steels containing Sn and Sb in acid chloride corrosion media, can act as inhibitors of anode reaction. Moreover, the Sn and Sb elements can also work synergistically with Cu to form a continuous and dense Sn-Sb-Cu oxide layer to protect the substrate [16,18,20].…”
Section: Introductionmentioning
confidence: 99%